The role of foreign aids and income inequality in poverty reduction : A sustainable development approach for Africa? - Alao, Rasheed O.; Alola, Andrew A. (Springer, 2022)
In the last decades, international interventions mostly through foreign aids have consistently been directed toward sustainable development objectives such as reduction of poverty in African countries. Thus, this study investigates the effect of foreign aids and income inequality in poverty reduction in Africa for 1990–2016. The novelty lies in the investigation of the effectiveness of aid remittances to Africa from the United Nations and Organization for Economic Cooperation and Development (OECD) which has previously been overlooked in extant studies. By using the system Generalized Method of Moments, the study showed that the interaction of inequality with the United Nations Development Programme (UNDP) funds and OECD Official Development Assistance is not statistically significant. Meanwhile, the interventions from the UNDP funds and OECD Official Development Assistance statistically yield significant and expected results of reducing poverty in the poor continent. However, the study surprisingly failed to establish that remittances from the UNDP have significantly mitigated poverty in Africa. Importantly, this study presents a significant policy guide for the governments and the stakeholders and recommends that the donor agencies adopt poverty-reduction, and income distribution-based criteria for the allocation of their resources to reduce poverty in the continent.
Keywords: Foreign aids; income inequality; SDGs; poverty; Africa; sustainable development; fi=Taloustiede|en=Economics|